Productive performance of five lines of Leghorn type hens and two diallelic crosses. - Alda, Tânia Baratto Lopes de; Costa, Paulo T. C.; Lopes, Juarez Morbini; Toledo, Geni Salete P. de (Pesquisa Agropecuaria Brasileira, 2014)
An experiment involving five pure lines of white Leghorn hens was conducted to evaluate their productive performance, compared with two crosses derived from two of them and a commercial strain. The research was done at the poultry section of "Departamento de Zootecnia at Universidade Federal de Santa Maria, RS, Brazil, from August 1983 to September 1984. When the pullets reached 20 weeks of age they were set in laying cages (eight pullets per cage), in an arrangement of eight treatments, with six replicates each. They were fed a diet with 16,5% crude protein and 2,800 Kcal EM/kg. The analysed data were: daily feed intake, body weight, egg production, egg weight, egg mace, feed conversion, feed efficiency, egg specific gravity and Haugh units. The results showed similar productive performance of the lines C, E, F, and G compared to the commercial strain, in spite of the low production of this group of hens. The body weight of two cross lines CE and EC were significantly higher than all the other lines, showing effects of heterosis for this variable, which probably caused their low productive performance.
Keywords: pullets; laying cages; protein; heterosis